Enhancing the competitiveness of Pinge tourism village: Integrated strategies for sustainable rural destination development - Nadera, Putu Melia Chandra Dewi; Nadra, Nyoman Mastiani; Ariningsih, Ni Putu (Journal of Commerce, Management, and Tourism Studies, 2025)
This study aims to formulate and analyse effective strategies to promote Pinge, a tourist village in Tabanan, Bali, as a competitive and sustainable rural tourism destination. The research adopts a qualitative descriptive approach, utilizing data collected through observations, in-depth interviews with stakeholders (including local community members, tourism managers, and government officials), focus group discussions, and document analysis. SWOT (Strengths, Weaknesses, Opportunities, Threats) and Analytical Hierarchy Process (AHP) methods are employed to identify internal and external factors influencing Pinge’s tourism development and to prioritize strategic actions. The analysis reveals that Pinge possesses significant natural, cultural, and agricultural assets, supported by strong community participation and the unique subak irrigation system. However, challenges such as limited marketing capacity, insufficient public facilities, and low digital literacy hinder optimal promotion. The study concludes that integrated strategies—such as capacity building for human resources, digital marketing optimization, collaborative partnerships, and the development of thematic tourism products—are essential for enhancing Pinge’s visibility and visitor appeal. Strengthening community-based organizations (Pokdarwis), improving infrastructure, and leveraging local wisdom (Tri Hita Karana) are also critical for long-term sustainability. The findings provide practical recommendations for policymakers, tourism managers, and local communities to foster inclusive growth and sustainable destination management in rural Bali.